2016
DOI: 10.1111/1460-6984.12260
|View full text |Cite
|
Sign up to set email alerts
|

Assessing school‐aged children's inference‐making: the effect of story test format in listening comprehension

Abstract: The results suggest that children are more likely to make target inferences if prompted during presentation of the story, and that this format is particularly facilitative for younger children and for local coherence inferences. This has implications for the design of comprehension assessments as well as for supporting children with comprehension difficulties in the classroom.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 37 publications
4
21
1
2
Order By: Relevance
“…This is in line with research demonstrating that shared reading has positive effects on listening skills (e.g. Freed 2017;Isbell 2004). Research of Freed (2017) showed that asking questions before, during, or after reading results in improvements in listening comprehension skills.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is in line with research demonstrating that shared reading has positive effects on listening skills (e.g. Freed 2017;Isbell 2004). Research of Freed (2017) showed that asking questions before, during, or after reading results in improvements in listening comprehension skills.…”
Section: Discussionsupporting
confidence: 90%
“…Freed 2017;Isbell 2004). Research of Freed (2017) showed that asking questions before, during, or after reading results in improvements in listening comprehension skills. Especially asking questions during reading seems to be effective in the case of young children (Freed 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Esto es, la reposición de conceptos necesarios para dotar de mayor coherencia a la oración que se está leyendo, durante la comprensión de un texto esta soportada por recursos de almacenamiento y de almacenamiento y procesamiento concurrente de memoria de trabajo. Resultados similares han sido encontrados en relación a la comprensión de textos en general tanto en niños como en adultos (Hannon, 2012;Loosli, Buschkuehl, Perrig, & Jaeggi, 2012;McVay & Kane, 2012;Wang & Gathercole, 2013) y también vinculados a la generación de inferencias (Barreyro et al, 2012;Currie & Cain, 2015;Freed & Cain, 2016;Pérez, Paolieri, Macizo, & Bajo, 2014;Prat et al, 2016).…”
Section: Discussionunclassified
“…Para lograr esta representación, el lector debe conectar ideas provenientes de diferentes partes del texto e integrarlas (Abusamra, & Joanette, 2012), esto es, debe realizar inferencias y conexiones entre la información literal explícita (Elbro & Buch-Iversen, 2013;van den Broek & Kendeou, 2008). La generación de inferencias se refiere a la activación de información que no se encuentra explícitamente enunciada durante la lectura para dar mayor coherencia a la oración focal que se está leyendo (Carlson et al, 2014;Freed & Cain, 2016;van den Broek, Risden, Fletcher, & Thurlow, 1996).…”
Section: Introductionunclassified
“…Inferences draw on information in the text, as well as information outside of the text, such as vocabulary and background knowledge. Local coherence inferences are necessary in order to integrate information from adjacent pieces of text, whereas global coherence inferences are used to fill in details not explicitly stated that are needed to construct a globally coherent representation of text meaning, for example inferences about themes, morals, and settings (Currie & Cain, 2015;Cain & Oakhill, 1999;Freed & Cain, 2017;Long & Chong, 2001). Inference making in general is critical to successful reading and listening comprehension in children both concurrently and longitudinally, over and above cognitive factors such as general ability and memory (Oakhill & Cain, 2012;Cain, Oakhill, & Bryant, 2004;Florit, Roch, & Levorato, 2014;Kim, 2016).…”
mentioning
confidence: 99%